Economic Growth, Population, and Policy Strategies : Its Effects on CO2 Emissions - Aminata, Jaka; Nugroho, S. B. M.; Atmanti, Hastarini Dwi; Agustin, Esther Sri Astuti Soeryaningrum; Wibowo, Agus; Smida, Ali (International Journal of Energy Economics and Policy, 2022)
This research work has been focused on China and India. Both Countries has a big number in population in the world and the rate of economic growth has been increasing every year. However, this is still accompanied by air pollution (CO2 emissions). Therefore, this study aims to analyze the relationship of population and GDP to CO2 emissions in China and India in the 1984-2014 timeframe and provide policy recommendations related to the problem being analyzed. Estimates use VECM to analyze the data collected. The results of the study show that in China and India, GDP and population in the short and long term have a positive effect on CO2 emissions and provide policy recommendations on willingness to pay for industry and willingness to accept for the community. The Environmental Kuznets Curve hypothesis was not confirmed in the case of China and India.